The Influence of The Green Hospital Implementation Policy on The Energy Saving Behavior of XYZ Hospital Employees Using The Theory of Planned Behavior Approach - Asmawati, Dika; Adisasmito, Wiku Bakti Bawono; Basabih, Masyitoh (UI Scholars Hub, 2024)
This research uses the Theory of Planned Behavior as the theoretical framework to analyze the relationship between the implementation of green hospital policy and energy-saving behaviors of employees in the hospital environment. The study's sample consists of 150 permanent employees, and the statistical data are analyzed using the Structural Equation ModelingPartial Least Square (SEM-PLS) technique. The analysis results indicate that implementing the green hospital policy influences the supportive factors of behavior: attitudes, subjective norms, and perceived behavioral control. However, the tests also reveal that subjective norms do not positively correlate with the energy-saving behaviors of employees at the hospital. The mediation analysis shows that attitudes and perceived behavioral control mediate between the green hospital policy and the intention to save energy. In contrast, subjective norms do not significantly mediate the relationship. As organizations strive for sustainability, these insights offer valuable guidance for refining policies and interventions that promote energy conservation among management and hospital staff.